Developing a conceptual framework related to managerial decision making capability factors in adopting technological innovation within Malaysian construction SMEs: research methodology - Mahdzir, Mazura; Syed Khuzzan Alhabshi, Sh Mazlina (Penerbit UTHM, 2015)
The motivation for one’s organisation to adopt any new technologies might differ across size, fields and countries. The adoption of any technologies has been largely influenced by managerial decision making capability. Realizing the importance of having sound and agile decision making and its effects towards one’s organisation when deciding to adopt any new technology, the exploration of managerial decision making capability (e.g skills, attitude, behavior etc) has become a main concern of the researcher, especially within the context of Small and Medium Enterprises (SMEs) in the Malaysian construction industry. This paper aims to describe the research methodology in developing a conceptual framework related to managers’ decision making capability factors that could help them understanding the influencial factors that affects their behavioural decision making. Thus, to achieve this, this study need to fulfil the following objectives (i) to examine an appropriate research methodology that suits with this research context (ii) to critically justify the flow of research methodology as summarized in the methodological framework. The development of the framework adopts a qualitative methodology to gain better information from managers using a case study research design from multiple SMEs specifically within the Malaysian construction industry. The research techniques adopted will be further elaborated, including the process of triangulating the research findings with other various sources of evidences.This paper also describes the process in reviewing the data via cross case analysis before validating the framework that have been theorised based on technological innovation and managerial-based researches. It is hoped that the development of this framework would lead managers to understand their level of adoption capability with respect to technological innovation, so that they can improve their capability adoption decision by planning an appropriate strategy.